Gray Matter Volume of a Region in the Thalamic Pulvinar Is Specifically Associated with Novelty Seeking - Stam, Daphne; Huang, Yun-An; Van den Stock, Jan (Frontiers in Psychology, 2018)
Personality reflects the set of psychological traits and mechanisms characteristic for an individual. Geno-neuro-biologically inspired personality accounts have proposed a set of temperaments and characters that jointly compose personality profiles. The present study addresses the link between neurobiology and personality and investigates the association between temperament traits and regional grey matter volume. Furthermore, the specificity of these associations as well as the underlying components that drive the association are addressed. One hundred and four participants completed the Temperament and Character Inventory (TCI) and underwent structural magnetic resonance brain imaging. The participants included premanifest carriers of Huntington disease, as this population is associated with temperament-related neuropsychiatric symptoms. Voxel-based multiple regression analyses on grey matter volume revealed a significant specific positive correlation between a region in the left thalamic pulvinar and novelty seeking score, controlled for the other traits (Pheight<.05, FWE-corrected). No significant associations were observed for the other temperament traits. Region of interest analyses showed that this association is driven by the subscale NS2: impulsiveness. The results increase the knowledge of the structural neurobiology of personality and indicate that individual differences in novelty seeking reflect the structural differences observed in the brain.